Role of extracellular matrix in muscle repair and regeneration - Chaturvedi, Vishal (Curtin University, 2014)
Extracellular matrices (ECMs) play important structural and mechanical roles in muscle tissue. They are also critical for normal muscle homeostasis, but it is poorly understood how individual matrix proteins, or the mix of ECM proteins found in vivo affect myoblast behaviour. Aspects of this question have been examined in this thesis using both matrices from skeletal muscle and artificial scaffolds prepared from silk proteins. The ability of these surfaces to support myoblast proliferation and differentiation was examined using a murine myoblast cell line and primary human skeletal muscle myoblasts.